RANCANGAN STRATEGI DUKUNGAN INOVASI PERTANIAN DI WILAYAH PERBATASAN KABUPATEN ACEH BESAR BERBASIS INTEGRASI AHP-SWOT - Rachman Jaya; Lamhot E. Pakhpahan; Muhammad Ismail (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
Desain of Agricultural Innovation Support Strategy in The National Border Area of Aceh Besar District Based on AHP-SWOT Integration. The research was conducted at Pulo Aceh Sub District, Aceh Besar District. The objective of this study is to obtain the design of development national border area at Aceh Besar District based on integration of AHP-SWOT analysis. In this study system approach was applied because of complexity problem and using expert survey. Numbers expert were 5 with background from researcher, academics and practitioners. The result of study showed that strength aspects consisted of aviability and suitability (0.623), weakness was lack of facilities (0.54), opportunity was availability of agricultural technology innovations (0,67) and threat were migration (0.80) and the absence of institutional agricultural systems (0.2). Strategy options can be used based on priority scales to develop national border area at Aceh Besar District are (1) Optimizing agriculture land by innovation (0.31), (2) Increasing of farmers’ capacity by technically guide of farming system and (3) Providing technical guide for farmers to determine priority scale of agricultural business (0.18). Keywords: border area, agriculture innovation, AHP-SWOT ABSTRAK Penelitian dilaksanakan di Kecamatan Pulo Aceh, Kabupaten Aceh Besar. Tujuan studi adalah menghasilkan rancang bangun dukungan inovasi pertanian wilayah perbatasan di Kabupaten Aceh Besar berbasis integrasi AHP-SWOT. Pendekatan yang digunakan adalah sistem karena kompleksitas kegiatan yang melibatkan beberapa pemangku kepentingan. Pakar yang terlibat berjumlah 5 orang dengan latar belakang peneliti, akademisi dan praktisi. Hasil penelitian menunjukan bahwa kekuatan adalah ketersediaan dan kesesuaian lahan (0,623), kelemahan adalah keterbatasan sarana dan prasarana pertanian (0,54), peluang dicerminkan dari tersedianya inovasi teknologi pertanian spesifik lokasi (0,67) serta ancaman adalah migrasi penduduk (0,80) dan belum adanya kelembagaan sistem pertanian (0,2). Opsi strategi yang ditawarkan berdasarkan skala prioritas untuk pembangunan wilayah perbatasan di Kabupaten Aceh Besar adalah (1) Melakukan optimalisasi lahan pertanian dengan inovasi teknologi pertanian, bobot (0,31), (2) Melakukan Peningkatan Kapasitas petani melalui bimbingan teknis sistem usaha tani (0,22), dan (3) Melakukan bimbingan teknis kepada petani dalam menentuan skala prioritas usaha pertanian (0,18).Kata kunci: wilayah perbatasan, inovasi pertanian, AHP-SWOT